2005
DOI: 10.1210/jc.2004-2386
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Hepatic Conversion of Dehydroepiandrosterone (DHEA) Sulfate to DHEA: In Vivo and in Vitro Studies

Abstract: Dehydroepiandrosterone (DHEA) sulfate (DHEAS) is the most abundant steroid in the human circulation and is thought to be the circulating hydrophilic storage form of DHEA. It is generally accepted that DHEA and DHEAS inter-convert freely and continuously via hydroxysteroid sulfotransferases and steroid sulfatase and that only desulfated DHEA can be converted downstream to sex steroids. Here we analyzed DHEA/DHEAS interconversion in vivo and in vitro. We administered oral DHEA (100 mg) and iv DHEAS (25 mg) to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 23 publications
0
32
0
1
Order By: Relevance
“…Accordingly, DHEAS was found to serve as a circulating storage pool for the generation of DHEA in peripheral target tissues of sex steroid action. However, while exogenous administration of DHEA in humans yields ample generation of both active sex steroids and DHEAS (20), we have previously shown that the administration of DHEAS does not result in appreciable levels of DHEA or active sex steroids (146,147). This suggests that DHEA sulphation is a permanent inactivating step and that the reverse reaction, cleavage of DHEAS to DHEA by STS, does not have a major impact on circulating steroid concentrations.…”
Section: Acrd (Hexose-6-phosphate Deficiency)mentioning
confidence: 88%
“…Accordingly, DHEAS was found to serve as a circulating storage pool for the generation of DHEA in peripheral target tissues of sex steroid action. However, while exogenous administration of DHEA in humans yields ample generation of both active sex steroids and DHEAS (20), we have previously shown that the administration of DHEAS does not result in appreciable levels of DHEA or active sex steroids (146,147). This suggests that DHEA sulphation is a permanent inactivating step and that the reverse reaction, cleavage of DHEAS to DHEA by STS, does not have a major impact on circulating steroid concentrations.…”
Section: Acrd (Hexose-6-phosphate Deficiency)mentioning
confidence: 88%
“…T is metabolized to E 2 by aromatase (CYP19). In humans, DHEA levels peaks in the morning (Hammer et al, 2005). DHEA-S levels are reduced in patients with advanced nonalcoholic fatty liver disease (NAFLD) (Charlton et al, 2008; Tokushige et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously assumed that DHEA and DHEAS are continuously interconverted, with DHEAS serving as a circulating pool for reactivation to DHEA, and ultimately sex steroids. However, this concept was called into question by studies suggesting that DHEA sulfation by the enzyme DHEA sulfotransferase, SULT2A1, is the predominant reaction, and the conversion back to DHEA through the enzyme steroid sulfatase is only a rare occurrence (1, 2), except for distinct tissues with ample steroid sulfatase activity, such as placenta and cancers of prostate, breast, endometrium, and colon (3). …”
mentioning
confidence: 99%